Fostering place-shaped responsibilities for biodiversity: an analytical framework with insights from the UK Overseas Territories - Montana, J (Elsevier, 2022)
Accelerated human impacts on the earth system bring urgency to the question of how responsibility can be appropriately and justly distributed across scales and actors. Drawing together theory from international relations and human geography with empirical analysis on responsibilities for biodiversity, this paper has two aims: to develop a framework for examining responsibilities for biodiversity that is applied to the context of the UK Overseas Territories; and to draw out broader lessons for thinking about environmental responsibilities more generally. The analysis draws particular attention to the importance of place-shaped responsibilities for biodiversity, which emerge as localised narratives of responsibility that take account of the enabling and resisting conditions that matter in particular places. Applied in the context of biodiversity governance, this suggests a need to join up policy issues, embed equity, explore multiple meanings, bridge pro-active and retrospective responsibilities, and enhance the role of the social sciences in enabling responsibilities.